Sunthi Siddha Jala (Ginger medicated water) as a Preventive Seasonal Intervention for Kapha-Related Disorders: Evidence from a Randomized Controlled Trial - Rasane, Shital R.; Abhijeet Amritkar, Vd. Shital; Paliwal, Amit Ashok (Journal of Neonatal Surgery, 2025)
Seasonal changes are known to exert a profound influence on human physiology, often leading to disturbances in metabolism, digestion, and immune balance. In Ayurveda, Vasanta Rutu (spring season) is described as a critical period during which Kapha dosha undergoes aggravation, manifesting as loss of appetite, lethargy, heaviness of the body, excessive salivation, cough, cold, and respiratory congestion. Classical texts recommend Sunthi Siddha Jala (medicated water prepared with dry ginger) as part of Rutucharya for mitigating these symptoms. However, clinical evidence evaluating its efficacy in a systematic manner remains limited. The present study aimed to assess the preventive and therapeutic effect of Sunthi Siddha Jala in reducing Kapha-related symptoms during Vasanta Rutu. A randomized controlled, open-label, parallel-group clinical trial was conducted on 60 volunteers, of which 55 completed the study. Participants were randomly allocated into two groups: Group A received Sunthi Siddha Jala daily, and Group B received plain potable water, for a period of 28 days. Symptoms of Kapha vitiation were documented at baseline and reassessed on Day 3, 7, 14, 21, and 28 using standardized symptom grading scales. Data were analysed using the Mann–Whitney U test. The results revealed that Group A experienced significantly faster and more complete relief in Kapha-related symptoms compared to Group B (p < 0.05). By the 21st day, all participants in Group A achieved remission of key symptoms such as agnisadan (loss of appetite), praseka (excessive salivation), aalasya (laziness), gaurava (heaviness), shaitya (feeling of cold), shlathangatwa (sluggishness of the body), shwas (breathlessness), kasa (cough), and atinidra (excessive sleep). In contrast, Group B showed only partial improvement even by Day 28. Importantly, no adverse effects were reported. The study concludes that Sunthi Siddha Jala is a safe, cost-effective, and clinically effective measure for preventing and managing Kapha aggravation during Vasanta Rutu. Its use not only reflects classical Ayurvedic wisdom but also aligns with modern insights into the pharmacological benefits of ginger. Further large-scale studies with objective biochemical parameters are recommended to validate and expand these findings